THE LEIOGNATHUS (TELEOSTEI): THEIR SPECIES, STOCKS, AND FISHERIES IN INDONESIA, WITH NOTES OF THE BIOLOGY OF LEIOGNATHUS SPLENDENS (CUVIER) - Pauly, Daniel (Marine Research in Indonesia, 1977)
Species of the family Leiognathidac in the Indo-Pacific area are often considered trash fish but are readily accepted in Indonesia, where about 50,000 tons were landed in 1975, 14,000 tons of which originated from the Malacca Strait area. The Western Jawa Sea, Karimata Strait and Indonesia's South China Sea stocks are underfished or, partially, even virgin and production from these stocks might be more than 100,000 tons a year. The leiognathid stocks, having their highest stock densities in very shallow waters (peak at 25 m depth) are easily overfished by trawling, while the bagan (lift-nets) tend to underfish them. In East Jawa, there is an annual periodicity in the fishery which is correlated with the rainfall, the peak landings being from December through March, while landings are lowest from July to September. Leiognathus splendens (CUVIER) makes up most of the leiognathid stock (90% and more). The main feature of the biology of this species ? growth, reproduction and food are briefly discussed. A short selected bibliography of the Leiognathidae is given.